School Principal Leadership In Improving Teacher Performance In SMPN 1 Banda Aceh And SMPN 8 Banda Aceh - Phuja Tawilla Septina; Bahrun Bahrun; Niswanto Niswanto (STKIP Singkawang, 2024)
The leadership style of the principal affects how well the school performs as a whole. The general pattern or course of action that the principle takes, which is seen as a tactic for raising teacher professionalism in order to achieve the next objective, which will build a pattern and an integral unity, is known as the principal's leadership. The purpose of this study is to determine how performance is enhanced by the principal's leadership. instructor at Banda Aceh SMPN 1 and Banda Aceh SMPN 8. This study employs a qualitative methodology using a descriptive research design. Techniques for gathering data include documentation, interviews, and observation. Using methods for data reduction, data presentation, and conclusion-making, qualitative descriptive analysis is the data analysis approach applied. According to research findings, it was discovered that: (1) programs designed and implemented to enhance the performance of teachers, such as those that involve training or improving soft skills for teachers, educational seminars, workshops for teachers, MGMP, KKG, awarding excellence in teaching, adding incentives for teachers, and giving them the chance to use IT devices to solve problems that arise during teaching and learning activities; (2) The principal's plan to raise teacher performance includes: offering incentives, recognizing exceptional teachers with prizes, introducing teacher incentives, educational seminars, MGMP, and teacher workshops; (3) The following are barriers to better teacher performance that school administrators must overcome: insufficient funds, time, or motivation; moreover, they lack the assistance of professionals who can conduct workshops or offer training in a language that is easily understood by teachers. The provision of suitable infrastructure that facilitates engaging, successful, and efficient teaching and learning activities is one of the supporting variables in the interim.